Analysis of psychometrical properties of the scale of social anxiety of the neurotic disturbances questionnaire - L. I. Tsidik (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Psychodiagnostic measuring instruments created within the framework of the classical theory of tests are distinguished by the instability of all psychometric parameters. Therefore, there arose the need to use modern scientifically grounded approaches for designing techniques that lack these shortcomings. The purpose of the study: to carry out an analysis of the psychometric properties of the scale of social anxiety of the questionnaire of neurotic disorders. A total of 296 people were tested. The main statistical method of work is the metric Rush system. Results: the approval of the scale of social anxiety possess an adequate constructual validity, measures of difficulty points are in the range from -2 to +2 logits, the scale is one-dimensional, has a relatively balanced metric structure, the reliability index is 0.83, the scale is able to differentiate the three levels of expression of the construct.